Entrepreneurship and Culture - Freytag, Andreas; Thurik, Roy (Springer Berlin Heidelberg, 2010)
The book is an innovative compilation of papers that explore the relationship between cultural features and entrepreneurship. The relative stability of differences in entrepreneurial activity across countries suggests that other than economic factors are at play. The contributions to this edited volume deal with the foundations of entrepreneurship and with the effects of different cultural settings on the incidence and success of entrepreneurs. Topics are individual decision making in a cultural context, regional aspects of entrepreneurship, cross-country differences, and the influence of culture on entrepreneurial activity
Keywords: Entrepreneurship; Economics, general; Regional and Cultural Studies; Industrial and Organizational Psychology; Economics; Culture-Study and teaching; Applied psychology; Internationaler Vergleich; Kulturelle Identität; Aufsatzsammlung